Design and control of a bidirectional interlinking converter for grid energy storage - Foo, Desmond De Ming (Nanyang Technological University, 2023)
In this report explained the technique of the current controlled bidirectional interlinking converters (BIC) for grid energy storage. Grid energy storage is the key to increase the penetration level of intermittent renewable generation. For example, solar photovoltaic and wind power in power system. Most energy devices such as batteries and supercapacitor demand a bidirectional DC/AC power converters as the interface to the gird. The design and control of such an interfacing or interlinking converters are paramount importance to the performance of grid energy storage systems. This project aims to develop simulation models as well as down-scaled experimental prototype for such a bidirectional interlinking. Advanced control algorithm will also be proposed to realize some ancillary services of energy storage in the power system. For example, frequency regulation/support, current control and power quality improvement to maximise the market values. The control algorithms will be programmed into a digital signal processor and tested in a hardware in the loop simulation environment.